A Comparative Study on Financial Performance between Islamic and Conventional Banking in Indonesia During the COVID-19 Pandemic - Mochammad Ilyas Junjunan; Ajeng Tita Nawangsari; Arta Agustin Melania; Agus Purnomo Ahmad Putikadyanto (IAIN Salatiga, 2021)
The COVID-19 pandemic has had an impact on all aspects of life, including Indonesian banking. Furthermore, there has been a rapid growth of both Islamic and conventional banking industries. Therefore, this study aims to analyze the diﬀerences in the ﬁnancial ratios of capital adequacy ratio, non-performing loans/non-performing ﬁnancing, return on asset, return on equity, operating expense to operating income, as well as loan to deposit ratio/ﬁnancing todeposit ratio of Islamic and conventional banking during the COVID-19 pandemic. Acomparative analysis method was used with a quantitative approach, and data analysis was carried out using the independent sample t-test and the Mann-Whitney rank test. The results showed that during the COVID-19 pandemic, there were signiﬁcant diﬀerences in the ﬁnancial performance ratios of capital adequacy ratio, non-performing loans/non-performing ﬁnancing, return on asset, return on equity, operating expense to operating income, and loan to deposit ratio/ﬁnancing to deposit ratio for both Islamic and conventional banking. Moreover, conventional banking tends to have better ﬁnancial performance compared to Islamic bankingduring the COVID-19 pandemic. The implication of this study is that the public can ﬁnd out the ﬁnancial position of both Islamic and conventional banks and make comparisons to ascertain which one has a better ﬁnancial position in times of crisis.